On the identity of some poorly known lithobiid centipedes described by Karl Verhoeff (Chilopoda: Lithobiomorpha) - Stoev, Pavel (Zootaxa, 2005)
The present paper considers the taxonomic status of the poorly known European centipedes Lithobius dollfusi Verhoeff, 1901, L. lapadensis Verhoeff, 1900 and L. karamani Verhoeff, 1937 described by the prominent German zoologist Dr. Karl Wilhelm Verhoeff, using types currently housed in the Museum für Naturkunde, Berlin. Re-examination of the types revealed the following new combination and synonymy: Harpolithobius dollfusi (Verhoeff, 1901) comb.n. = H. intermedius Matic, 1958 syn.n. Lithobius lapadensis and L. karamani are re-described and illustrated and their taxonomic position discussed.